A survey of East Palaearctic Gnaphosidae (Araneae). 1. On the Berlandina Dalmas, 1922 (Gnaphosinae) from Mongolia and adjacent regions - Marusik, Yuri M.; Fomichev, Alexander A.; Omelko, Mikhail M. (Zootaxa, 2014)
Five new species of Berlandina Dalmas, 1922 are described from Mongolia: B. koponeni sp. n. (♂), B. mishenini sp. n. (♂), B. nakonechnyi sp. n. (♂), B. ovtsharenkoi sp. n. (♂♀) and B. yakovlevi sp. n. (♂♀). Nine other species occurring in Mongolia and adjacent Russia, China and Kazakhstan are illustrated: B. caspica Ponomarev, 1979; B. hui Song, Zhu & Zhang, 2004; B. nabozhenkoi Ponomarev& Tsvetkov, 2006; B. nenilini Ponomarev& Tsvetkov, 2006; B. potanini (Schenkel, 1963); B. saraevi Ponomarev, 2008; B. schenkeli Marusik & Logunov, 1995; B. spasskyi Ponomarev, 1979 and B. ubsunurica Marusik & Logunov, 1995. The female of B. ubsunurica is described for the first time. Fourteen species occurring in northern Asia (Kazakhstan-Mongolia) are split into 5 species groups.